2023
DOI: 10.3390/pathogens12030414
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lymphocyte Subpopulations, Clinical Features and Inflammatory Markers during Severe COVID-19 Onset

Abstract: Background: Dysregulation of the immune response in the course of COVID-19 has been implicated in critical outcomes. Lymphopenia is evident in severe cases and has been associated with worse outcomes since the early phases of the pandemic. In addition, cytokine storm has been associated with excessive lung injury and concomitant respiratory failure. However, it has also been hypothesized that specific lymphocyte subpopulations (CD4 and CD8 T cells, B cells, and NK cells) may serve as prognostic markers for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…An increase in the relative abundance of activated CD4 + T, CD4 + TCM, and NK T cells was prominent, which may be considered as one of the factors for an active T cell response, however, the CD8 + T cell population (CD8 + TCM and CD8 + TEM) was reduced in COVID-19-positive individuals when compared with healthy and recovered individuals. Several studies have shown that both CD4 + T and CD8 + T cell decrease is associated with disease severity ( 19 22 ). However, in our dataset, only CD8 + T cells, not CD4 + T cells, were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the relative abundance of activated CD4 + T, CD4 + TCM, and NK T cells was prominent, which may be considered as one of the factors for an active T cell response, however, the CD8 + T cell population (CD8 + TCM and CD8 + TEM) was reduced in COVID-19-positive individuals when compared with healthy and recovered individuals. Several studies have shown that both CD4 + T and CD8 + T cell decrease is associated with disease severity ( 19 22 ). However, in our dataset, only CD8 + T cells, not CD4 + T cells, were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early prediction of critical illness is particularly important. The COVID-19 diagnostic and treatment guidelines clearly indicate that Lymphopenia is an early warning indicator for severe COVID-19 ( 15 ). Many studies have shown that elevated D-dimer is associated with severe COVID-19 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes, including T cells and natural killer (NK) cells, play important roles in the immune response against SARS-CoV-2 infection [3]. Changes in the proportion of lymphocyte subpopulations could potentially serve as indicators of disease severity and clinical outcomes.…”
mentioning
confidence: 99%